Competency, Attitude and Islamic Teachers Issue in Using Computer for Learning and Teaching Process - Aini, Khairatul; Tamuri, Ab Halim; Syafril, Syafrimen (Khalifa Journal of Islamic Education, 2019)
This research is aimed to know phases of competency, attitude and Islamic teachers issue in using computer for learning process. This research uses qualitative and quantitative mixed method (explanatory mixed methods design). Quantitative data were obtained from sixty-four Islamic teachers by using questionnaire and were analyzed with descriptive statistics through SPSS Windows Version 15.0. Meanwhile, Qualitative data were taken from eight teachers through intensive interview and were analyzed thematically by using software NVivo 7. Results of the research show that the teachers competency in using computer is still at poor phase (Mean = 2.32, SD = 0.22), while their attitude toward that issue in learning process is very positive (Mean = 3.94, SD = 0.36). Furthermore, Qualitative results find that there are four important themes related with the issue enforced by the teachers in applying computer to the learning process. Such are; i) lower self-competency to use computer, ii) lack of computer facilities provided in shool, iii) lack of computer training for the teachers, and iv) lack of time in designing computer-based learning due to over-task issue in the school.